1996
DOI: 10.1111/j.1365-2621.1996.tb12212.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Escherichia coli by Carbon Dioxide under Pressure

Abstract: Thermal inactivation of Escherichia coli was studied under CO 2 pressures of 1.2, 2.5, and 5 MPa at 25, 35, and 45ЊC. Two phases were observed in the destruction curves. The earlier stage was characterized by a slow rate of inactivation, which increased sharply at the later stage. An increase of pressure and/or temperature enhanced the antimicrobial effects of CO 2 under pressure. The effects on cell structure were studied by scanning electron microscopy and the specific mechanism of action appeared to be rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
97
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 15 publications
13
97
0
1
Order By: Relevance
“…; therefore, it is a suitable agent for controlling food spoilage microorganisms (22,23,29). In recent years, the influence of high-pressure CO 2 on the vegetative cells of various species has been demonstrated (1,3,4,7,8,9,10,11,13,14,18,20,28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…; therefore, it is a suitable agent for controlling food spoilage microorganisms (22,23,29). In recent years, the influence of high-pressure CO 2 on the vegetative cells of various species has been demonstrated (1,3,4,7,8,9,10,11,13,14,18,20,28).…”
mentioning
confidence: 99%
“…The antimicrobial effects of compressed CO 2 have been extensively studied to elucidate the mechanism. In such studies, the death of target cells has been variously explained as follows: the acidification by dCO 2 may cause the inactivation of key enzymes related to the essential metabolic process (1,5,6,7,13,18), the extraction of intracellular substances such as hydrophobic compounds in the cell wall and cytoplasmic mem- brane may result in microbial death (18), cell rupture due to the expansion of CO 2 within the cells may induce a loss of viability (3,26), the damage to the cell membrane due to swelling with compressed CO 2 may kill the cells, or an "anesthesia effect" may induce the inhibition of metabolic systems (13,14,27). Authors have demonstrated that the inactivation power of CO 2 was much greater in a continuous treatment (sudden decompression) under high-pressure carbonation than in a batch treatment (slow decompression) (26).…”
mentioning
confidence: 99%
“…The inoculated media was immediately placed in a 4 L pressure vessel (Alloy Products Corp, Waukesha, WI) and made anaerobic through the use of a GasPak ™ EZ Anaerobe Container System Sachet (BD, Franklin Lakes, NJ).The serum bottles in the vessels were then pressurized to 1.0 MPa in the field with ultrapure CO 2 . Previous work has shown that CO 2 is very effective sterilant (Nakamura et al, 1994;Isenschmid et al, 1995;Ballestra et al, 1996;Shimoda et al, 1998;Hong and Pyun, 1999;Erkmen, 2000;Spilimbergo and Bertucco, 2003;Watanabe et al, 2003;Damar and Balaban, 2006;Oule et al, 2006Oule et al, , 2010Song et al, 2007). With this in mind, we reasoned that cultures grown at very high CO 2 pressures would likely result in a sterilization of most viable microorganisms, especially those accidentally introduced through contamination.…”
Section: Field Samplingmentioning
confidence: 99%
“…They are phylogenetically diverse, perform a variety of metabolic activities, and share very little evolutionary relationship to each other (Song et al, 2007;Bringel et al, 2008;Arioli et al, 2009). Capnophiles have been isolated from a variety of habitats including plants, mammalian cavities, wastewater, and animal rumens (Ballestra et al, 1996;Bringel et al, 2008;Ueda et al, 2008;Arioli et al, 2009). While a large degree of attention has been given to these bacteria for food and disease studies, little has been given to their presence and environmental significance in the deep subsurface.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the HPCD-treated E. coli cells showed that increasing the treatment time decreases total proteins. In previous investigations, HPCD caused damage to the cytoplasmic membrane (Ballestra et al, 1996;White et al, 2006;Kim et al, 2009;Spilimbergo et al, 2009). Therefore, the protein loss in the HPCD-treated E. coli cells in this study was mainly ascribed to leakage of proteins into the media due to damage to the cytoplasmic membrane.…”
Section: Resultsmentioning
confidence: 99%